2019
DOI: 10.1016/j.tips.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence for Clinical Trial Design

Abstract: Clinical trials consume the latter half of the 10 to 15 year, 1.5-2.0 billion USD, development cycle for bringing a single new drug to market. Hence, a failed trial sinks not only the investment into the trial itself but also the preclinical development costs, rendering the loss per failed clinical trial at 800 million to 1.4 billion USD. Suboptimal patient cohort selection and recruiting techniques, paired with the inability to monitor patients effectively during trials, are two of the main causes for high tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
252
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(256 citation statements)
references
References 51 publications
2
252
0
2
Order By: Relevance
“…Unlike the current state-of-the-art embryo classification algorithms, [8,10] deep learning provides full automation and standardization of embryo classification, which are both important for clinical adoption. [25,26] The SHIFRA classifiers, which provide early evaluation of blastulation and implantation potential, are the first step toward the development of a decision-making tool that will provide a personalized, multistep, embryo transfer strategy. [27,28] Namely, given a finite number of embryos obtained from a patient and their assessed quality, this tool will specify the multistep order and timing of embryo transfers (including transfers of multiple embryos), as well as which embryos are to be cryopreserved for subsequent transfers.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the current state-of-the-art embryo classification algorithms, [8,10] deep learning provides full automation and standardization of embryo classification, which are both important for clinical adoption. [25,26] The SHIFRA classifiers, which provide early evaluation of blastulation and implantation potential, are the first step toward the development of a decision-making tool that will provide a personalized, multistep, embryo transfer strategy. [27,28] Namely, given a finite number of embryos obtained from a patient and their assessed quality, this tool will specify the multistep order and timing of embryo transfers (including transfers of multiple embryos), as well as which embryos are to be cryopreserved for subsequent transfers.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of 15 and 50 equidistant snapshots were collected from the set of 150 snapshots. According to Tab 4. it is observed that −T ∆S calculated on 15 and 50 sample snapshots leads to a similar −T ∆S calculated on the whole set.…”
mentioning
confidence: 59%
“…AI/ML technologies have begun to be deployed within key steps of clinical trial design from study preparation to execution, leading to trial success rate improvement. 8 For instance, IBM Watson has developed a system for Clinical Trial Matching, which uses the large quantity of structured and unstructured patient electronic medical record data and the abundance of available trials to create detailed profiles of clinical findings for the patients to compare to trial eligibility criteria. As the system incorporates all the complex protocol criteria to consider, it eliminates the need to manually sort through and analyze complex enrollment criteria and enables clinicians to optimize their search for clinical trials for an eligible patient or for finding patients eligible for a given trial.…”
Section: Ai/ml For Clinical Trial Outcome Prediction and Designmentioning
confidence: 99%